2013
DOI: 10.1063/1.4825174
|View full text |Cite
|
Sign up to set email alerts
|

Self-Consistent Ornstein-Zernike Approximation (SCOZA) and exact second virial coefficients and their relationship with critical temperature for colloidal or protein suspensions with short-ranged attractive interactions

Abstract: We focus on the second virial coefficient B 2 of fluids with molecules interacting through hard-sphere potentials plus very short-ranged attractions, namely, with a range of attraction smaller than half hard-sphere diameter. This kind of interactions is found in colloidal or protein suspensions, while the interest in B 2 stems from the relation between this quantity and some other properties of these fluid systems. Since the SCOZA (Self-Consistent Ornstein-Zernike Approximation) integral equation is known to y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Sometimes, (κσ) −1 is used as an effective range of the HCAY model. 61 The main quantity characterizing the AO potential, which is often used in the context of colloid-polymer mixtures, is the size ratio η between the colloid and the polymer (for details see, e.g., 32,66 ). Valadez-Pérez et al 32 have argued that short-range HCAY and AO potentials with κσ 3 and η 1.25, respectively, correspond to effective ranges λ eff ≤ 1.25, assuming a constant b c 2 value of −1.5 (Eq.…”
Section: Square-well Fluids and The Elcs For Simple Fluidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sometimes, (κσ) −1 is used as an effective range of the HCAY model. 61 The main quantity characterizing the AO potential, which is often used in the context of colloid-polymer mixtures, is the size ratio η between the colloid and the polymer (for details see, e.g., 32,66 ). Valadez-Pérez et al 32 have argued that short-range HCAY and AO potentials with κσ 3 and η 1.25, respectively, correspond to effective ranges λ eff ≤ 1.25, assuming a constant b c 2 value of −1.5 (Eq.…”
Section: Square-well Fluids and The Elcs For Simple Fluidsmentioning
confidence: 99%
“…where Π is the osmotic pressure of the system. While for many model potentials, including HCAY, AO and patchy particles, the applicability, possible extensions and restrictions of the ELCS have been studied by simulations, 32,46,60,61 the ELCS has hardly been assessed for systems as complex as proteins. 52 Though it has been found that scaling gas-liquid binodals of protein solutions to the critical points results in a master curve, 40,62 most experimental values of the second virial coefficient b c 2 are systematically smaller than those predicted by VL and NF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These aggregation kinetic models include mass-action kinetic approaches, 100 fixed-point approaches, 101 and stochastic approaches. 102 Other examples of continuum models include the application of theories based on statistical mechanics such as the Self-Consistent Ornstein-Zernike Approximation, Kirkwood-Buff solution theory, and Wertheim’s perturbation theory for evaluating high-concentration phenomena such as protein self-assembly, 103 liquid–liquid phase separation, 104 protein interactions, 105 , 106 and solution rheology. 107 , 108 …”
Section: Types Of Protein Modelsmentioning
confidence: 99%
“…Also, the first virial coefficients are used in the development of liquid theories, like density functionals or integral-differential equations. [6][7][8] Virial series are not only a major tool for simple and molecular fluids, but for colloidal systems. This systems are a mixture of two type of particles with a characteristic big size difference.…”
Section: Introductionmentioning
confidence: 99%